Numerical simulation of Bluetooth signal short-hop for the measurement while drilling near-bit - Zhiwei Chu; Quanxin Li; Xinxin Fang; Long Chen; Yunhong Wang; Jiguan Zhang; Wenchao Yan (Scientific Reports)
Abstract Near-bit information has become increasingly critical in Measurement While Drilling (MWD) operations. Efficient data transmission between the downhole near-bit unit and the surface control platform is a key factor in MWD technology. Particularly, short-range near-bit data transmission serves as the communication foundation between these two components. The feasibility of using Bluetooth as a wireless short-hop solution for near-bit MWD has not been thoroughly investigated. To address this gap, this study proposes a Bluetooth-based wireless transmission system, where transmitting and receiving modules are installed at opposite ends of a non-magnetic drill pipe. ANSYS EM finite element simulation software was employed to model the system and analyze key factors influencing Bluetooth signal transmission. Using the control variable method, the following aspects were evaluated: (1) Bluetooth signal strength loss under varying conditions; (2) The impact of rotational speed on signal attenuation; (3) The effect of a sleeve plug on signal propagation. The results indicated that: (1) Bluetooth can effectively transmit near-bit data during drilling operations; (2) Increasing transmission power enhances received signal strength, but the improvement plateaus beyond a certain threshold; (3) The wireless Bluetooth short-hop module proves to be a viable solution for near-bit data transmission; (4) Water-based environments significantly degrade Bluetooth signal stability. While transmission remains stable in dry conditions, the presence of drilling mud introduces signal instability and increased noise; (5) Drill string rotation has negligible influence on Bluetooth signal transmission; (6) The plug does not have a shielding effect on the transmission of the signal, the receiving end can still receive the signal, the plug has little impact on the transmission of Bluetooth signal. With the increase of the thickness of the plug, the return loss of Bluetooth signal is smaller, and the signal strength of the receiving end is stronger. It testified that the plug was conducive to the improvement of the signal strength of the receiving end in the short-distance transmission of Bluetooth signal and could reduce the dissipation of Bluetooth signal. The research results could provide reference for the development and improvement of near-bit MWD equipment.